Efforts of the Communist Party of Lithuania to liquidate the partisan movement - Truska, Liudas (Genocidas ir rezistencija, 1998)
The Central Committee of the All–Union Communist Party of the Soviet Union, which repeatedly discussed the activities of the LSSR’s party organisation in the post–war years, demanded the “immediate fulfilment of its most pressing task – the liquidation of banditism. However, all the deadlines have passed, and the Lithuanian partisan movement, despite suffering grievous losses, with the support of the nation has not been broken, let alone liquidated. The situation remains tense,” the leadership of the LSSR’s NKVD stated in the summer 1947. It was in this context that the following document appeared: the Resolution of the Central Committee of the Lithuanian Communist Party (LKP(b)) of 12 December 1947 on the intensification of the anti–partisan struggle in the republic.
Keywords: communist party; Soviet Union; repressive structures; armed resistance